(a/9)=(a-1)/8

Simple and best practice solution for (a/9)=(a-1)/8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a/9)=(a-1)/8 equation:


a in (-oo:+oo)

a/9 = (a-1)/8 // - (a-1)/8

a/9-((a-1)/8) = 0

(-1*(a-1))/8+a/9 = 0

(-1*9*(a-1))/(8*9)+(8*a)/(8*9) = 0

8*a-1*9*(a-1) = 0

9-a = 0

(9-a)/(8*9) = 0

(9-a)/(8*9) = 0 // * 8*9

9-a = 0

9-a = 0 // - 9

-a = -9 // * -1

a = 9

a = 9

See similar equations:

| (x/18)=-5/6 | | 12x=1x+9 | | 20t^2+18t-5=0 | | 15-5x-8-6x=11-2x+2 | | -(3y+3)-(-2y-4)=-2 | | y^2+18y-81=0 | | 12/15=x/32 | | x/14=12/7 | | 6/7t=48 | | (((x-5)/5)-1)=((x-13)/6) | | 11-3x=-6x+2 | | 3z+7=z+10 | | cot(x)=2.4 | | log(8)(k-8)=2 | | x^3-x^2+15*x+17=0 | | V=Bcy | | 4sin(2x)+2=0 | | 0.2x+4.4=3.3 | | (1128*2)+(120*3)=x+(x*0.2) | | -2(a-6)=-36 | | z=0.06-50/6 | | 70(-8/5) | | 2y+3=33 | | x^2-4x+4+x^2-18x+81=x^2 | | 6(c+2)-x=4(x+4)+7 | | 6-6n+3n=42-84 | | ab-9a+b-45= | | -20/-4= | | 6-6n+3n=42-8 | | 5-97-09= | | 7x^2+27x+18=0 | | 4(n+6)+4n=8+8(2n+6) |

Equations solver categories